The Long Shadow of Childhood Adversity: The Mediating Role of Theoretical Processes in the Relationship Between Adverse Childhood Experiences and the Victim-Offender Overlap - Leban, Lindsay (Victims & offenders, 2025)
Few criminological phenomena are as well-documented as the victim-offender overlap, yet its underlying sources remain poorly understood. Using data from the National Longitudinal Study of Adolescent to Adult Health, this study examines the role of Adverse Childhood Experiences (ACEs) in the overlap in victimization and offending in early adulthood, while evaluating potential mediating theoretical processes. Results indicate that ACEs significantly influence the victim-offender overlap, extending beyond their impact on victimization or offending alone. The pathway from ACEs to the victim-offender overlap operates, in part, through low self-control, deviant peer association, drug use, and weakened social bonds.